Impact of Capital Structure and Macroeconomics on The Performance of BPR in Mediation Managerial Skills (Case Study of PD BPR Bahteramas South Konawe) - Jumaing, Ardilla; Syaifuddin, Dedy Takdir; Asraf, Asraf (International Journal of Management and Education in Human Development, 2024)
The research aims to determine the impact of capital structure and macroeconomics on BPR performance mediation by managerial ability (Case Study of PD BPR Bahteramas South Konawe). The type of research used is a quantitative approach. Data was collected using observation methods, documentation methods and library study methods. The data analysis technique used is SEM PLS. The results of this research show that capital structure does not have a significant influence on the performance of PD BPR Bahteramas Konawe Selatan. There is no significant influence of capital structure on managerial ability. Macroeconomic conditions have a significant positive influence on managerial ability. Macroeconomic conditions do not have a significant influence on the performance of PD BPR Bahteramas Konawe Selatan. Managerial ability is unable to mediation the influence of capital structure on the performance of PD BPR Bahteramas Konawe Selatan. Managerial ability is proven to significantly mediation the relationship between macroeconomic conditions and the performance of PD BPR Bahteramas Konawe Selatan.